China tripping encountering the everyday in the People's Republic - Murray, Jeremy A.; Link, E. Perry 1944- (Eugene Perry).; Pickowicz, Paul (Lanham Rowman & Littlefield, 2019)
This unique book is the first to bring together a group of influential China experts to reflect on their cultural and social encounters while travelling and living in the People’s Republic. Filling an important gap, it allows scholars, journalists, and businesspeople to reflect on their personal memories of China. Private experiences—vivid and often entirely unanticipated—often teach more about how a society actually works than a planned course of study can. Such experiences can also expose the sometimes naïve misconceptions visitors often bring with them to China. China experts relate stories that are always interesting but also more: they tell not just anecdotes but telling anecdotes. Why are there no campus maps? (Because, if you don’t know where you’re going and why, you don’t need to be here.) What’s the allure of Mickey Mouse? (He could break all sorts of rules and get away with it.) What’s a sworn brother in China? (Somebody who fights for your honor even when you’re not looking.) Covering nearly a half-century from 1971 to the present, these stories open a vivid window on a rapidly evolving China and on the zigzag learning curve of the China trippers themselves.--Provided by publisher.
Dirty underwear Paul G. Pickowicz -- China was not utopia / Anita Chan -- Broom? Silk? / Perry Link -- Where are the child psychologists? / Martin King Whyte -- Third-world students in China / Donald C. Clarke -- Young journalists / Stephen R. MacKinnon (1978-80) -- The operation of power / Donald C. Clarke -- The rehabilitation of sociology / Martin King Whyte -- A night with the post office guys / James M. Hargett -- Stamp connections / Wendy Larson -- Buying socks / Perry Link (1979-80) -- A single room / Vera Schwarcz -- Death of a tourist / Morris Rossabi -- Expats / Stephen R. MacKinnon (1979-80) -- No signs, no maps / Charlotte Furth -- Stop overexciting the masses! / Thomas D. Gorman -- Bureaucracy and nosiness / Donald C. Clarke -- The stupidest thing I did in China / Suzanne Cahill -- Representative of the bourgeoisie / Charlotte Furth -- Famous American spy / Suzanne Cahill -- Encountering Shandong / Joseph W. Esherick -- High in Tibet / Melinda Liu -- My father's hometown / Mayfair Yang -- High rise counterculture / Paul G. Pickowicz -- Second uncle and his wife / Mayfair Yang -- Manuscript / Stanley Rosen -- The local officials: whiffs of the Qing Dynasty / Mayfair Yang -- A fitting chair / Jennifer Anderson -- Thank you very much / Dru C. Gladney -- Where are we going? / Thomas D. Gorman -- Old lady / Stanley Rosen -- Books on secondary extraction / Geoffrey Ziebart -- Making assumptions / Jeffrey N. Wasserstrom -- Internal document / Stanley Rosen -- Brotherhood / Geoffrey Ziebart -- Mickey Mouse at Peking U / David Moser -- Reading tea leaves / Richard P. Madsen (1988-89) -- Eating bitterness / Vera Schwarcz -- Clayderman to Cui Jian / James A. Cook -- Catholic church in Tianjin / Richard P. Madsen -- Welcome our foreign friends / David Moser -- Cradle of the revolution / Andrew D. Morris -- A night at the Movenpick / Perry Link -- Opium war / Andrew D. Morris -- Special powers / Jeremy Brown -- Relationships, not names / David Moser -- Estrangement / Nick Admussen -- Living in the White House / Marketus D. Presswood -- The loudness of lambs / Dru C. Gladney (2003-04) -- Men's world / Jeremy Brown -- Malleable rules / Philip F. Williams -- Tashkurgan / Justin M. Jacobs -- Mainlander / Jeremy A. Murray -- Avoiding long lines / Paul G. Pickowicz -- Hainan fishing captain / Jeremy A. Murray -- Black is beautiful! / Marketus D. Presswood -- Darth Vader and the triceratops / Maggie Greene -- A phone call from the party secretary / Melinda Liu -- Afterword / Minxin Pei.
Keywords: Americans -- 20th century. -- China; Americans -- 21st century. -- China; China -- Description and travel; China -- Social life and customs -- 1976-2002.; China -- Social life and customs -- 2002-.